Stomatal resistance, xylem water tension and chlorophyll concentration of soursop genotypes (Scientia Agricola, 2001)
Ecophysiological variables have great influence, not only on the vegetative behavior, but mainly in relation to yield characteristics. Leaf diffusive resistence to vapor, xylem water tension and chlorophyll concentration were evaluated for two soursop genotypes (Morada and Comum) cultivated under field conditions. The trial was carried out during two seasons (September and December/1998), in a commercial orchard of Paudalho, PE, Brazil. An entirely randomized experimental design was used, with six replicates per genotype. In each replicate two healthy and completely developed leaves, located on the medial one third of the canopies were selected. These leaves were directly exposed to solar radiation. During three consecutive days on each season, and at the most evaporative activity time (between 12:00 a.m. and 2:00 p.m.), the transpiration (E), leaf diffusive resistance to vapour (Rs), leaf temperature (LT), xylem water tension (psiw) and the chlorophyll a and b concentrations were measured. Differences in the seasonal behavior were verified in relation to gaseous changes, psiw and LT between those genetic materials. Correlations between psiw and E, and between psiw and LT were found. Relative humidity showed correlation with LT and with Rs. Comum soursop was most efficient photosynteticly, decreasing the chlorophyll b degradation by luminosity incidence. In general, genotypes Morada and Comum showed different behavior for all evaluated ecophysiological parameters. psiw is a good parameter to distinguish soursop genotypes. Rs can be used as a parameter for differentiation of environmental adaptation among soursop genotypes in higher evaporative requirement seasons.